PENINGKATANPERKEMBANGANKOGNITIFMELALUIMETODE EKSPERIMENANAKUSIA5-6TAHUNDITKISLAMIYAH PONTIANAKTENGGARA - Sriyati, Sriyati; Halida, Halida; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract Children cognitive development can be increased by doing experimental activities because by doing experiments, children are able to engage actively in activities and use concretely media that can stimulate children cognitive development, so the children in TK Islamiyah Pontianak still can’t do the experiment by them self, they can’t find the cause due to the occurrence of something/ telling the results of experiments conducted, teachers are not able to understand how to improving children cognitive. The general purpose of this study is to increase the cognitive development through the experimental method.Thisresearchwasclassroomactionresearch.SubjectsandLocationofthisstudy areteachersand childrenaged 5-6years.From theresult of research and discussion can be concluded as follows (1) Learning plan made by the teacher to improve children cognitive development through experimental method has been prepared in accordance with the purpose of research and fulfill the preparation steps in accordance with the curriculum 2013. (2) The implementation of learning to improve the children development Cognitive have been implemented in accordance with the planning of learning that has been made. (3) The result of improvement of children cognitive developmentthroughexperimentalmethodcategorizedasverygooddevelopment. Keywords:Cognitive,Experimental,EarlyChildhood